ANALISIS STRUKTUR DAN FUNGSI CERITA RAKYAT HUI CILEMBU DI KABUPATEN SUMEDANG SEBAGAI UPAYA PELESTARIAN SASTRA LISAN - Yulia Winarsih; Kuswara; Ece Sukmana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The folklore of Hui Cilembu is one of the oral literature treasures in Sumedang Regency that contains moral values and etiological history. However, along with modernization, the existence of this oral tradition faces the risk of extinction if not scientifically documented. This study aims to dissect the narrative structure, identify the function of the story for the community, and formulate efforts for its preservation. The approach used is qualitative narratology by applying Vladimir Propp's Morphology of the Folktale theory. The research data was sourced from the oral text of the Hui Cilembu folklore, which was analyzed through the scheme of narrative functions and the character's spheres of action. The results showed that the story's narrative is constructed by a moral testing structure manifested in Propp's dominant functions, namely the Initial Situation (\(α \)), the First Function of the Donor or Test (D), the Hero's Reaction (E), and Magic/Punishment/Reward (F/W/K). An overlapping of roles occurs where the Prince of Sumedang acts as both the donor/tester and the hero. Sociologically, this story functions as a means of moral education (didactic) and legitimization of the origin of local commodities. The implications of this structural analysis contribute directly to the preservation of oral literature through academic textual documentation and provide teaching materials based on local wisdom for primary education in the related area.